FRI0045 Evaluation of serum protein levels at baseline as predictors of response to methotrexate in patients with early rheumatoid arthritis: results from swefot trial population. (12th June 2018) - Hambardzumyan, K.; Hamsten, C.; Idborg, H.; Lourido, L.; Saevarsdottir, S.; Nilsson, P.; van Vollenhoven, R.F.; Jakobsson, P.-J.
Abstract : Background: Methotrexate (MTX) is a standard first-line therapy option for patients with early rheumatoid arthritis (eRA). However, a substantial proportion of patients still do not respond to MTX. Objectives: To identify biomarkers for prediction of response to MTX. Methods: We analysed a group of patients (n=135) with eRA from the Swedish Pharmacotherapy (SWEFOT) trial population. Baseline serum levels of 177 proteins were profiled using 380 antibodies in a suspension bead array format. Median fluorescent intensity (MFI) levels of the proteins were subsequently analysed for association with achievement of low 28-joint disease activity score (DAS28 ≤3.2) after 3 months of MTX therapy (primary outcome). Proteins that remained significant in multivariate model were analysed using receiver operating characteristic (ROC) curve analysis for cut-off definition of MFI and categorisation into high and low categories. Proportion of patients with primary outcome between the generated categories were compared using Chi-squared test. Results: In multivariate analysis, serum levels of two of the 177 proteins at baseline, matrix metalloproteinase 7 (MMP-7) and alpha-chain of fibrinogen (FGA) were significantly different among patients who achieved or not achieved low DAS28 at 3 months. ROC curve analysis revealed AUC of 0.692 for MMP-7 and 0.699 for FGA (p<0.001; figure 1A). ROC curve-based dichotomisation indicated that of patients with low versus high levels of either MMP-7 or FGA, 60% versus 24% and 58% versus 22%, respectively, achieved low DAS28 (p<0.001; figure 1B and C). Among patients with low categories of both proteins, 79% achieved low DAS28 at 3 months, while only 18% of those in high categories for both proteins (p<0.001; figure 1D). Validation in the COMBINE cohort with available MMP-7 data (whose concentration was measured by different method) did not confirm results from the SWEFOT trial. Conclusions: Low levels of MMP-7 and FGA at baseline were associated with better clinical outcome in eRA patients. Following further characterisation, such biomarkers would be of high clinical relevance for the optimisation of treatment of RA. Disclosure of Interest: K. Hambardzumyan: None declared, C. Hamsten: None declared, H. Idborg: None declared, L. Lourido: None declared, S. Saevarsdottir: None declared, P. Nilsson: None declared, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Pfizer, UCB, Consultant for: AbbVie, AstraZeneca, Biotest, BMS, Celgene, GSK, Janssen, Lilly, Novartis, Pfizer, UCB, P.-J. Jakobsson: None declared